(untitled) (Strathmore Law Review, 2022)
In 2014, Kenya enacted the Marriage Act to amend and consolidate various laws on marriage and divorce. Among the amendments introduced was the irretrievable breakdown ground of divorce alongside more traditional fault-based grounds. The court in CWL v HN noted that the introduction of this ground had effectively done away with the need for petitioners to provide evidence of matrimonial fault in divorce proceedings. Despite this, the Act still maintains traditional fault grounds for divorce not only as independent grounds but also as factors to be considered when determining whether a marriage has irretrievably broken down. The author contends that this retention of fault-based requirements reflects an outdated position and contradicts the thinking behind the introduction of irretrievable breakdown as a divorce ground. This study, therefore, proposes adopting a uniform no-fault divorce system premised on irretrievable breakdown. To better align this system with the dual objective of protecting individual dignity while also safeguarding the dignity and sanctity of marriage, the study proposes a model that includes a mandatory requirement to attempt reconciliation before petitioning for divorce.